2022
DOI: 10.3390/s22041601
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Object Detection Algorithm-Based Braille Image Generation System for the Recognition of Real-Life Obstacles for Visually Impaired People

Abstract: The global prevalence of visual impairment due to diseases and accidents continues to increase. Visually impaired individuals rely on their auditory and tactile senses to recognize surrounding objects. However, accessible public facilities such as tactile pavements and tactile signs are installed only in limited areas globally, and visually impaired individuals use assistive devices such as canes or guide dogs, which have limitations. In particular, the visually impaired are not equipped to face unexpected sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Overall, it performed well, correctly identifying barriers with an accuracy of 80.69%. A living-based indoor navigation system for the visually impaired that includes item extraction, object identification, a braille conversation algorithm, and output generation was proposed by Lee et al [ 49 ]. They found that the average accuracy was 85%, the average duration for braille discussion was 6.6 s, and the accuracy of object identification was 90% or higher.…”
Section: Assistive Systems Useful For Navigation For Visually Impaire...mentioning
confidence: 99%
“…Overall, it performed well, correctly identifying barriers with an accuracy of 80.69%. A living-based indoor navigation system for the visually impaired that includes item extraction, object identification, a braille conversation algorithm, and output generation was proposed by Lee et al [ 49 ]. They found that the average accuracy was 85%, the average duration for braille discussion was 6.6 s, and the accuracy of object identification was 90% or higher.…”
Section: Assistive Systems Useful For Navigation For Visually Impaire...mentioning
confidence: 99%